Analisis atas Respon Netizen pada Postingan Akun @Quranreview di Instagram - Muhammad Rifat Al-Banna; Moch. Ihsan Hilmi (Jurnal Iman dan Spiritualitas, 2022)
Living Quran studies various social events related to the Koran, which has become a tradition in forming a local entity. This study explores the living Quran, which contains interpretations through digital media on the Instagram account @QuranReview. This study examines the netizen's response to posts regarding the interpretation in the @QuranReview account post. Amid the trend of interpreting the Koran on social media, the @QuranReview account has succeeded in attracting the attention of netizens through the presentation of religious content in the form of interpretation with the style of language, diction, and nuances typical of the millennial generation. The analysis structure used in this research is descriptive analysis based on a socio-anthropological approach. The findings from this study are that the netizen's response to the commentary in the @QuranReview Instagram account has three effects that can provide benefits to netizens, including cognitive products that can offer new insights in understanding interpretations, then practical effects that can directly cause aesthetic and emotional dimensions when Netizens deeply interpret performance and the behavioral results that can make changes in the behavioral perspective netizens even more.